Reinterpretation of religious and nationalism in Wasiat Renungan Masa: A hermeneutical approach to Hamzanwadis thought - Herman WIjaya; Andayani Andayani; Nugraheni Eko Wardani (Universitas Syiah Kuala, 2025)
This research explored the reinterpretation of the dimensions of religion and nationalism in Hamzanwadis Wasiat Renungan Masa. This research aimed to understand religious messages and nationalism in the context of changing times and reveal their relevance to the challenges of globalization and modernization. The problem in this study lay in the complexity of the relationship between the spiritual dimension and national identity that emerged in the text. This research method was a hermeneutic approach to analyze the text in depth using the data source of the text Wasiat Renungan Masa. Data collection techniques were based on literature studies and text analysis. Data analysis techniques involve in-depth interpretation to uncover hidden meanings. Data validation was performed through triangulation by comparing the results of the analysis with the views of literary experts. The results of this study indicated that the religiosity of Kiyai Hamzanwadi is inseparable from the spirit of nationalism; instead, both complement and strengthen each other. Religion is considered a source of inspiration that encourages individuals to fight for the interests of the nation and state, while nationalism is not only a concept of nationality but also an expression of loyalty to religious teachings. This research enriches the understanding of literatures role in expressing religious values, nationalism, and their relevance to identity and social change in Indonesia.